Usaha Menghormati Keberadaan Khalayak Televisi Swasta - Abrar, Ana Nadhya (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Gadjah Mada, 1997)
This article explores what the private televisions should do in order to appreciate the qistence of audience. The exploration has been done by using current theoretical and empirical understandings of the relationship between private television and its audience. The results suggest that the private television should: (1) present the na,vs stories about true love; (2) televise the realistic drama; (3) create program which is based on audiences world; (4) broadcart the art of lives more frequently; and (5) not exaggerating the scandal.